Persepsi dan Niat Berhenti Merokok pada Perokok Dewasa Berdasarkan Theory of Planned Behavior - Difa Annas Haqie; Dimas Heriyanto; Nur Halimah Tu Saddiah; Luthfi Aditya Yudistira Carera Budi Satria Wibawa (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
This study aims to understand the perceptions and intentions to quit smoking among adult smokers in the Special Region of Yogyakarta using the Theory of Planned Behavior (TPB) approach. TPB is employed to identify how attitudes toward smoking, subjective norms, and perceived behavioral control influence individuals’ intentions to quit smoking. This research uses a qualitative approach with a phenomenological design, exploring the experiences and subjective meanings of the participants. The research subjects consist of four adult smokers selected purposively. Data collection techniques involved semi-structured interviews and observations, while data analysis used triangulation methods. The results indicate two differing perspectives regarding smoking: some subjects emphasized the negative impacts such as disease risk, physical fatigue, and financial losses that motivated their intention to quit, whereas others continued smoking for reasons of relaxation, stress reduction, and social interaction. The social environment was shown to play a dual role, both weakening and strengthening the motivation to quit depending on the prevailing norms. At the individual control level, subjects were influenced by internal factors such as stress and nicotine addiction, as well as external factors like social support and smoke-free zone policies.